191k views
1 vote
2(x)+2(2)=2(x/2)-2(x)
Solve this please and show the steps!!!!!!

User Odelia
by
5.0k points

2 Answers

4 votes

Answer:-4/3

Explanation:

2(x)+2(2)=2(x/2)-2(x)

Remove brackets by multiplying through

2x + 4=x - 2x

Collect like terms

2x+2x-x=-4

3x=-4

Divide both sides by 3

3x/3=-4/3

x=-4/3

User TheStoneFox
by
6.1k points
3 votes

Answer:
x=-(4)/(3)

Explanation:


2(x)+2(2)=2((x)/(2))-2(x)

Remove all those parentheses by multiplying. Note: 2 and 2 cancel out.


2x+4=x-2x

Subtract 2x


4=x-2x-2x

Combine like terms;


4=-3x

Divide by -3


(4)/(-3)=x

Rewriting it;


x=-(4)/(3)

User Magicshui
by
5.8k points